AN AUDIT OF BOWEL PREPARATION IN ANORECTAL PROCEDURES AMONG SURGERY RESIDENTS (Journal of Medical & Health Sciences Review, 2025)
Objective: This study was designed to audit the adequate provision of Mechanical bowel preparation (MBP) in anorectal procedures and its effects on the overall post-operative outcome.Design: A retrospective data review for audit cycle and a prospective design for re-audit cycle.Place and duration of study: Department of surgery in Khyber teaching hospital Peshawar from January 2021 to December 2022.Methodology: As part of the audit process, we took approval from the hospital ethical committee and investigated the files of 100 patients, between January 2021 and December 2022, obtained from the medical record room to whom MBP was not given before surgery, irrespective of the type of disease. Then the re-audit cycle began where the same number of patients were added to the study between January 2022 and December 2022, their management done, MBP was given and post operative outcomes were documented through OPD follow up. Results: For both the audit and re-audit groups there was general male preponderance, 82% in audit and 74% in re-audit cycles respectively, and the mean age of the population was 37.4. Hemorrhoids and fistulas were the major pathologies seen in addition to a multitude of other anorectal disorders in the study. None of the candidates in the audit group were given MBP (kleen enemas). While in the re-audit group all patients were given 2 kleen enemas 6 hours apart before their surgeries and it was perceived that more than 90% of the patients had no symptomatology on fifth day post operative follow up.Conclusion: Even though many experts recommend avoidance of MBP in centers across the globe for it being obsolete and unnecessary, this prerequisite still provides good benefit in controlling post-surgery ailments.